Performance study of knowledge integration in marketing-oriented small and medium enterprises - Huang, Li Hua; Sun, Xi Ming (Nurture, 2024)
Purpose: This study aims to examine the impact of the knowledge fermentation field on the knowledge integration performance of marketing-oriented SMEs. This research will help develop more useful market policies for company management. Design/Methodology/Approach: This research focuses on marketing-oriented SMEs, conducting a survey among 700 employees from 421 such enterprises. The collected data were analyzed to understand the influence of the knowledge fermentation field on the knowledge integration performance of these enterprises. Findings: Knowledge management plays a crucial role in marketing-oriented SMEs especially in terms of knowledge integration. Effective knowledge management strategies significantly enhance the market adaptability and innovation capabilities of these enterprises. Conclusion: The knowledge fermentation field in marketing-oriented SMEs positively impacts the enterprise's knowledge integration performance. The relationship between the field of knowledge fermentation and the performance of knowledge integration in marketing-oriented SMEs is moderated by the knowledge spiral fermentation system. Research Limitations and Implications: The study primarily targets marketing-oriented SMEs in a specific region and may not be entirely applicable to other regions or different types of enterprises. The influence of temporal variations on business knowledge integration performance may not have been properly taken into account during data collection. Practical Implications: This study provides businesses with an effective tool for developing and comprehending knowledge creation and innovation in the spiral fermentation system model of the knowledge ecosystem in small and medium-sized marketing companies. It fosters a healthier development path for the knowledge ecosystem in these enterprises. Contribution to the Literature: This study proposes a new theoretical framework in the field of knowledge management for marketing-oriented SMEs. It offers new perspectives and theoretical support for understanding and enhancing knowledge management practices in SMEs by integrating the concepts of the knowledge ecosystem and knowledge integration performance.